2018
DOI: 10.1038/s41598-018-34858-x
|View full text |Cite
|
Sign up to set email alerts
|

SEPROGADIC – serum protein-based gastric cancer prediction model for prognosis and selection of proper adjuvant therapy

Abstract: Gastric cancer (GC) patients usually receive surgical treatment. Postoperative therapeutic options such as anticancer adjuvant therapies (AT) based on prognostic prediction models would provide patient-specific treatment to decrease postsurgical morbidity and mortality rates. Relevant prognostic factors in resected GC patient’s serum may improve therapeutic measures in a non-invasive manner. In order to develop a GC prognostic model, we designed a retrospective study. In this study, serum samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A recently published study suggested that the immunoScore signature could predict response to adjuvant chemotherapy in stage II and III GC patients in subgroup analysis, but the result was not validated [ 28 ]. Another two studies reported that serum biomarkers based model in GC patients from single-center could classify the patients who are suitable for chemoradiation or chemotherapy [ 29 , 30 ]. However, these models were conducted in a small sample size and were not independently validated.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study suggested that the immunoScore signature could predict response to adjuvant chemotherapy in stage II and III GC patients in subgroup analysis, but the result was not validated [ 28 ]. Another two studies reported that serum biomarkers based model in GC patients from single-center could classify the patients who are suitable for chemoradiation or chemotherapy [ 29 , 30 ]. However, these models were conducted in a small sample size and were not independently validated.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the six normalization proteins in a sample, the normalized LFQ value of each protein was calculated by dividing its corrected LFQ value by NSF. where is the normalized LFQ of urinary protein j in sample s and is the corrected LFQ of the corresponding protein [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The geometric mean of the six ratios of the sample was then used as the normalization scaling factor (NSF) for that sample. The details of this method are also provided in previous studies [ 83 , 84 ].…”
Section: Methodsmentioning
confidence: 99%